Determinants of Stakeholder Support for Restorative Ecological Justice in Post-Presidential Regulation 5/2025 Forest Repossession: A Mixed-Methods Study in Riau, Indonesia - Indrayani; Moses Adi; Mesy Yulandari; Aziwarti (HM Publisher, 2025)
The promulgation of Presidential Regulation No. 5 of 2025 (Perpres 5/2025) marks a decisive shift in Indonesia's forest governance, replacing the fiscal-amnesty logic of the Job Creation Law with the actualization of State Control Rights through repossession of illegally occupied forest areas and severe administrative fines. Yet the determinants of stakeholder support for resolving such disputes restoratively rather than punitively remain untested. This convergent parallel mixed-methods study examined a 5,420-hectare spatial overlap in an anonymized Limited Production Forest within a major oil-palm-producing province of Sumatra, Indonesia. A powered perception survey (n=240) measuring procedural justice, distributive justice, tenurial security, institutional trust, and corporate accountability as predictors of support for a Restorative Ecological Justice model was triangulated with 15 key-informant interviews and Geographic Information System spatial data. Scale reliability was good to excellent (Cronbach's α 0.857–0.932). Support differed sharply across groups (one-way ANOVA F(3,236)=26.343, p<0.001, η²=0.251), with corporate affiliates far lower than farmers, officials, and civil society (Cohen's d=1.83). Multiple regression explained 57.1% of variance (R²=0.571, F(5,234)=62.38, p<0.001); tenurial security (β=0.425) and distributive justice (β=0.370) were the strongest predictors, followed by corporate accountability (β=0.173) and procedural justice (β=0.167). The study concludes that durable forest-conflict resolution requires pairing corporate repossession with earmarked ecological restoration and the transition of repossessed land into social-forestry schemes for smallholders, operationalizing restorative ecological justice within Indonesia's new enforcement regime.